Waterproof and anti-permeable building external wall insulation board and construction method thereof
Patent Information
- Application Number
- CN202610835251.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-10
- Publication Date
- 2026-11-03
AI Technical Summary
Existing building exterior wall insulation boards have problems such as insufficient interface adhesion, lack of self-healing ability of waterproof layer, serious water seepage in board joints and simple side drainage structure, resulting in insufficient durability and waterproof and seepage-resistant performance.
The system employs an interface transition layer containing silane coupling agent, a waterproof layer with nano-silica penetrating crystallization components, a stepped flow channel and hydrophobic flange design, and microcapsule self-healing sealant to form a multi-layered, multi-mechanism waterproof and seepage-proof structure.
It significantly improves the interfacial bonding strength, realizes the self-healing function of the waterproof layer, optimizes the side drainage performance, effectively prevents leakage at the board joints, extends the service life, and improves the waterproof and seepage-resistant performance.
Smart Images

Figure CN123025544A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building exterior wall insulation technology, specifically to a waterproof and seepage-resistant building exterior wall insulation board and its construction method. Background Technology
[0002] Building exterior wall insulation systems are an important component of building energy conservation. The application of exterior wall insulation boards is very common in northern my country. These boards effectively reduce heat transfer loss and improve energy efficiency. However, existing exterior wall insulation boards have many problems in practical applications, particularly deficiencies in waterproofing and seepage prevention, which seriously affect the durability of the insulation system.
[0003] Most common exterior wall insulation boards on the market currently use a layered structure combining an insulation layer and a waterproof layer. While this structure can provide insulation and waterproofing to a certain extent, it has the following technical problems: First, traditional insulation boards rely primarily on physical bonding between the insulation core material and the waterproofing and adhesive layers, lacking chemical bonding. Under long-term temperature cycling and humidity changes, the difference in the thermal expansion coefficients of the various layers can lead to shear stress at the interface. When this stress exceeds the interfacial bond strength, quality problems such as delamination and detachment occur. This phenomenon is particularly prominent on the exterior walls of high-rise buildings, where detached insulation board fragments can pose serious safety hazards.
[0004] Secondly, the waterproof layer formed by traditional waterproof coatings is a passive waterproofing mechanism, relying solely on its own density to prevent water penetration. Once the waterproof layer develops micro-cracks or is punctured, water will seep into the insulation layer along the cracks or puncture channels. Due to the lack of a self-repairing mechanism, these seepage channels will gradually widen, eventually leading to the failure of the insulation system. More importantly, micro-cracks in traditional waterproof layers are difficult to detect with the naked eye, and users often only discover them when the seepage problem has become quite serious, missing the optimal time for repair.
[0005] Third, gaps must be left between adjacent insulation boards during installation to accommodate temperature deformation. These gaps are weak points in waterproofing, and the traditional method is to fill them with sealant. However, ordinary sealant has limited adhesion strength to the insulation board substrate, and under long-term ultraviolet radiation and temperature cycling, the sealant is prone to aging, cracking, and loss of sealing function. In addition, poor drainage design at the board gaps allows rainwater to easily seep into the wall, causing indoor leaks.
[0006] Fourth, traditional insulation boards typically have flat sides without any drainage design. Rainwater falls on the wall and flows along the sides of the insulation board, seeping into the seams under gravity and eventually penetrating the insulation layer. This side seepage problem is particularly severe during heavy rain, and simply filling with sealant is insufficient to effectively prevent it.
[0007] In summary, existing technologies have failed to effectively address a range of issues, including insufficient bonding strength at the interface of external wall insulation boards, lack of self-healing ability in the waterproof layer, severe water seepage at board joints, and rudimentary side drainage structures. Summary of the Invention
[0008] The primary objective of this invention is to provide a waterproof and seepage-resistant building exterior wall insulation board. By adding a specific silane coupling agent to the interface transition layer, the problem of insufficient interfacial adhesion is solved. The active defense and self-repair function of the waterproof layer is achieved through nano-silica penetrating crystallization components. The side drainage performance is optimized through stepped drainage channels and hydrophobic flanges. The leakage problem of board joints is solved through microcapsule self-healing sealant, thereby comprehensively improving the waterproof and seepage-resistant performance and service life of the exterior wall insulation board.
[0009] To achieve the above objectives, the present invention adopts the following technical solution: A waterproof and seepage-resistant building exterior wall insulation board includes, from the inside out, a base bonding layer, an insulation core layer, an interface transition layer, a waterproof and seepage-resistant layer, and a protective finishing layer.
[0010] The interface transition layer is made of polymer cement mortar containing silane coupling agent. The silane coupling agent used is γ-glycidyl etheroxypropyltrimethoxysilane, and its dosage in the polymer cement mortar is 1.5%-3.0% of the cement weight.
[0011] The waterproof and seepage-proof layer is formed by coating and curing a polymer waterproof coating containing nano-silica penetrating crystallization components. The nano-silica penetrating crystallization components are composed of nano-silica, crystalline active masterbatch and penetrating carrier in a weight ratio of 1:1.5-2.5:2.5-3.5.
[0012] The insulation board has a pair of opposite sides with stepped flow channels that extend along the height of the insulation board and have a hydrophobic flange at the outlet end.
[0013] Furthermore, the polymer cement mortar containing silane coupling agent, by weight, comprises: 100 parts silicate cement, 200-300 parts quartz sand, 3-8 parts redispersible latex powder, 1.5-3.0 parts γ-glycidyl ether oxypropyltrimethoxysilane, 0.2-0.5 parts cellulose ether, 0.5-1.0 parts water-reducing agent, and 40-55 parts water.
[0014] Furthermore, the polymer waterproof coating containing nano-silica penetrating crystallization components comprises, by weight: 40-55 parts of acrylate copolymer emulsion, 2-5 parts of nano-silica, 3-6 parts of flaky sericite powder grafted with polyurethane, 3-8 parts of crystalline active masterbatch, 6-14 parts of penetrating carrier, 1-3 parts of composite slow-release penetrating crystallization promoter, 1-3 parts of film-forming aid, 0.2-0.5 parts of defoamer, 0.3-0.8 parts of dispersant, and 15-25 parts of water. The crystalline active masterbatch is a mixture of activated calcium silicate and activated calcium aluminate in a weight ratio of 2-4:1; the penetrating carrier is a sodium methylsilanolate solution.
[0015] Furthermore, the preparation method of the surface-grafted polyurethane flake sericite powder is as follows: the flake sericite powder is dispersed in an ethanol aqueous solution, γ-aminopropyltriethoxysilane is added, and the mixture is stirred and reacted at 60-80℃ for 2-4 hours. After filtration and drying, aminated sericite powder is obtained. The isocyanate-terminated polyurethane prepolymer is dissolved in N,N-dimethylformamide, and aminated sericite powder is added. The mixture is reacted at 50-60℃ for 4-6 hours, and then centrifuged, washed, and dried to obtain the surface-grafted polyurethane flake sericite powder.
[0016] Furthermore, the composite slow-release permeation crystallization accelerator is composed of lithium carbonate, sodium fluorosilicate, and sodium dodecylbenzenesulfonate in a weight ratio of (2-4):(1-2):(0.5-1). Its preparation method is as follows: lithium carbonate and sodium fluorosilicate are pulverized and passed through a 200-mesh sieve and then mixed evenly to obtain a solid mixture; sodium dodecylbenzenesulfonate is dissolved in deionized water to prepare an aqueous solution with a mass fraction of 10%-15%; the solid mixture is added to the sodium dodecylbenzenesulfonate aqueous solution, ultrasonically dispersed evenly, and then spray-dried, controlling the inlet air temperature at 120-140℃, thus obtaining a composite slow-release permeation crystallization accelerator with a surfactant coating on its surface.
[0017] Furthermore, the insulation core layer is extruded polystyrene foam board or molded polystyrene foam board with a thickness of 30-80mm; the base bonding layer is polymer bonding mortar with a thickness of 3-5mm; the protective finishing layer consists of crack-resistant mortar base layer, alkali-resistant glass fiber mesh and finishing layer, with a total thickness of 5-8mm.
[0018] Furthermore, the cross-section of the stepped flow channel is stepped, including at least two steps, each step having a depth of 0.5-1.5mm and a width of 2-4mm; the hydrophobic flange is a triangular convex strip with a height of 1-2mm and a width of 2-3mm, and its surface is coated with a superhydrophobic coating.
[0019] Furthermore, the thickness of the interface transition layer is 2-4mm; the thickness of the waterproof and seepage-proof layer is 1.5-3.0mm, and the surface water contact angle of the waterproof and seepage-proof layer is greater than or equal to 120 degrees.
[0020] The insulation board construction method of the present invention includes the following steps: S1. Base treatment: Clean the surface of the exterior wall base, remove dust, oil stains and loose parts, fill cracks and holes with repair mortar, and cure until the moisture content of the base is less than or equal to 10%.
[0021] S2. Marking and positioning: Mark the horizontal and vertical baselines on the base wall to determine the installation position of the insulation board.
[0022] S3. Apply base bonding layer: Apply polymer bonding mortar to the inner side of the insulation board to form base bonding layer 1. Use strip bonding method or dot frame method for construction, and the bonding area is greater than or equal to 40%.
[0023] S4. Laying the interface transition layer: Apply polymer cement mortar containing silane coupling agent to the outer surface of the insulation core material layer and cure for 12-24 hours to form the interface transition layer.
[0024] S5. Apply a waterproof and seepage-proof layer: Apply a polymer waterproof coating containing nano-silica penetrating crystallizing components to the surface of the interface transition layer in two coats, with an interval of 4-6 hours between each coat, for a total thickness of 1.5-3.0 mm. Allow it to cure for 24-48 hours to form a waterproof and seepage-proof layer.
[0025] S6. Install insulation boards: Paste the coated insulation boards onto the base wall surface, with the board joint width controlled at 2-4mm, and align the stepped guide grooves of adjacent insulation boards.
[0026] S7. Anchoring and Fixing: Install anchor bolts on the insulation board. The anchor bolts penetrate the base bonding layer and the insulation core material layer and are anchored into the base wall. The anchoring depth is greater than or equal to 25mm, and the number of anchor bolts per square meter is greater than or equal to 6.
[0027] S8. Apply protective finishing layer: On the outside of the waterproof and seepage-proof layer, apply crack-resistant mortar base layer, lay alkali-resistant fiberglass mesh and finishing layer in sequence to form a protective finishing layer.
[0028] S9. Joint sealing: Fill the joints between insulation boards with sealant containing microcapsule self-healing agent. The microcapsule self-healing agent is epoxy resin microcapsules encapsulated in urea-formaldehyde resin. The amount of microcapsules is 3%-8% of the weight of the sealant.
[0029] Furthermore, in step S4, the coating thickness of the polymer cement mortar containing silane coupling agent is 2-4 mm. After coating, a notched trowel is used to scrape out the notches, the notch depth is 1-2 mm, the curing temperature is 5-35℃, and the relative humidity is greater than or equal to 60%.
[0030] Furthermore, in step S5, the thickness of the first coating layer is 0.8-1.5 mm, and the thickness of the second coating layer is 0.7-1.5 mm. After coating, the coating is cured for 24-48 hours at a temperature of 20±2℃ and a relative humidity of ≥65%. The nano-silica penetrating crystallization component penetrates into the capillaries of the interface transition layer after coating, with a penetration depth of ≥5 mm. It reacts with the free calcium ions in the interface transition layer to generate insoluble calcium silicate crystals, which block the capillary channels.
[0031] Furthermore, in step S9, the sealant containing the microcapsule self-healing agent is composed of silicone sealant and microcapsules. The microcapsules have a particle size of 50-200 micrometers and a wall thickness of 2-5 micrometers. When a microcrack with a width of less than or equal to 0.3 mm occurs at the board seam, the crack expands to the microcapsule, causing the microcapsule to rupture and release the epoxy resin repair agent. Under the action of ambient moisture, it cures and achieves self-repair of the microcrack.
[0032] The present invention has the following beneficial effects: (1) The methoxy group undergoes hydrolysis in an aqueous environment to generate silanol groups; the silanol groups undergo condensation reactions with calcium ions and hydroxyl groups in cement hydration products, forming stable Si-O-Ca chemical bonds between the inorganic minerals and the silanol groups. At the same time, the epoxy group undergoes ring-opening reactions with the polymer molecular chains in the redispersible latex powder under appropriate conditions to form COC covalent bonds. Through this dual chemical bonding, a molecular-level bridging channel is established between the inorganic cement matrix and the organic polymer. Traditional interface agents rely solely on physical interlocking, and the bonding strength is usually only 0.3-0.4 MPa, while this invention, through molecular-level bridging, increases the interfacial bonding strength to over 0.6 MPa, fundamentally solving the problem of insufficient bonding strength of traditional interface agents. This chemical bonding has high stability and durability, and the bonding strength will not significantly decrease even under long-term immersion and freeze-thaw cycles.
[0033] (2) Nano-silica has a very large surface area, typically between 200-400 square meters per gram. Carried by a sodium methylsiloxane solution as a permeation carrier, nano-SiO2 can penetrate into the capillaries of the interface transition layer 3, reaching a depth of over 5 mm. The nano-SiO2 entering the capillaries undergoes a hydration reaction with the free calcium hydroxide in the interface transition layer 3, generating insoluble hydrated calcium silicate gel. These gel-like substances fill the capillary channels, forming a dense waterproof barrier. Simultaneously, the active calcium silicate and active calcium aluminate in the crystalline active masterbatch undergo a secondary hydration reaction upon contact with water, generating needle-like ettringite crystals. These needle-like crystals intertwine and grow in the capillaries, further densifying the capillary structure. When microcracks appear in the waterproof layer, moisture seeps into the cracks and activates the unreacted crystalline active substances, generating new crystals to repair the cracks. This self-healing function gives the waterproof layer an intelligent response capability, greatly extending its service life.
[0034] (3) The stepped cross-section of the stepped guide channel 6 forms a multi-stage cascading structure, where the water flow experiences kinetic energy attenuation and changes in direction at each step. Multiple stagnant zones are formed between adjacent steps, where water remains and evaporates, preventing the formation of a continuous water flow channel. This multi-stage water-blocking effect is far superior to single-stage planar water-blocking; even if some water breaks through the upper barrier, it will still be intercepted by the lower layer. The hydrophobic flange 7 is located at the outlet end of the guide channel. When water gathers at the flange, it is thrown off the plate surface by the flange's overhanging action. The superhydrophobic coating has a contact angle exceeding 150 degrees, resulting in extremely low adhesion of water to the flange surface, further ensuring the throwing effect. The combined effect of these two elements significantly reduces the amount of water seeping from the plate side.
[0035] (4) Epoxy resin microcapsules encapsulated in urea-formaldehyde resin are dispersed in silicone sealant, with a particle size controlled at 50-200 micrometers and a wall thickness of 2-5 micrometers. When microcracks with a width of less than or equal to 0.3 mm occur at the joint due to temperature deformation or structural displacement, stress concentration occurs at the crack tip. This stress concentration acts on the nearby microcapsules, and when the stress exceeds the bearing limit of the microcapsule wall, the wall ruptures, and the internal epoxy resin repair agent is released. Driven by capillary force, the repair agent penetrates the entire length of the crack. The epoxy groups in the repair agent undergo a ring-opening curing reaction initiated by ambient moisture, re-bonding the crack. Compared with traditional sealants, microcapsule self-healing sealant can automatically repair microcracks without relying on manual intervention, maintaining long-term sealing performance.
[0036] (5) The active material source of the nano-SiO2 penetrating crystallization component is the free calcium ions in the interface transition layer. If the bonding between the interface transition layer and the insulation core material and the waterproof and seepage-proof layer is not strong, the crystallization material cannot exist stably in the interface area. The stepped flow channel and hydrophobic flange guide the water flow on the side of the plate away from the interface between the waterproof layer and the insulation core material, reducing the seepage pressure of the waterproof layer. The microcapsule self-healing sealant blocks the last possible seepage channel from the end. It is this multi-layered and multi-mechanism synergistic protection that enables the waterproof and seepage-proof performance of the present invention to reach a level that is difficult to achieve with the prior art.
[0037] (6) The flaky sericite powder grafted with polyurethane on the surface is arranged in parallel in the waterproof coating, forming a dense water-blocking channel, which greatly extends the penetration path of water. At the same time, the flexible segments of the polyurethane grafted on the surface endow the flaky sericite with excellent deformation following ability, which can effectively absorb and release the stress generated by the thermal expansion and contraction of the insulation board, prevent the formation of micro-cracks in the waterproof layer, and significantly improve the crack resistance and seepage prevention performance of the coating.
[0038] (7) The composite slow-release penetrating crystallization accelerator uses sodium dodecylbenzene sulfonate to spray-dry lithium carbonate and sodium fluorosilicate. After application, the surfactant film on the surface slowly dissolves in the alkaline pore water of the cement, precisely controlling the release rate of the accelerator. This allows the crystals to grow uniformly and deeply inside the capillaries, completely solving the industry problem of traditional penetrating crystallization materials reacting too quickly, causing surface scaling and whitening, and clogging capillaries. This improves the deep waterproofing and seepage prevention effect. Attached Figure Description
[0039] Figure 1 This is a structural schematic diagram of a waterproof and seepage-resistant building exterior wall insulation board and its construction method proposed in this invention; Figure 2 This is a partial structural schematic diagram of a waterproof and seepage-resistant building exterior wall insulation board and its construction method proposed in this invention; Figure 3 This is a flowchart illustrating the construction method of a waterproof and seepage-resistant building exterior wall insulation board and its construction method proposed in this invention.
[0040] The corresponding labels in the attached diagram are: 1. Base bonding layer; 2. Thermal insulation core layer; 3. Interface transition layer; 4. Waterproof and seepage-proof layer; 5. Protective finishing layer; 6. Stepped drainage channel; 7. Hydrophobic flange. Detailed Implementation
[0041] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0042] The specific implementation process is as follows: Example 1:
[0043] Please see Figure 1-3 The present invention provides a technical solution as follows: The insulation board in this embodiment is designed with dimensions of 1200mm × 600mm × 50mm, and extruded polystyrene foam board is used as the insulation core material. The base bonding layer 1 uses polymer bonding mortar, with a thickness controlled at 4mm. The polymer bonding mortar is a commonly used polymer-modified cement-based bonding material on the market, which has good bonding performance and water resistance.
[0044] Insulation core layer 2 uses extruded polystyrene foam board with a density of 32 kg / m³. 3 With a thermal conductivity of 0.028 W / (m·K) and a thickness of 50 mm, extruded polystyrene foam board possesses excellent thermal insulation properties and high compressive strength, making it a commonly used material for building exterior wall insulation. The boards should undergo necessary aging treatment before leaving the factory to ensure dimensional stability.
[0045] The polymer cement mortar formula for interface transition layer 3 is designed by weight as follows: 100 parts of ordinary Portland cement (P·O42.5); 250 parts of quartz sand (40-70 mesh); 5 parts of redispersible latex powder (ethylene-vinyl acetate copolymer type, RE5010N); 2.0 parts of γ-glycidyl ether oxypropyltrimethoxysilane (KH560); 0.3 parts of hydroxypropyl methylcellulose (HPMC MH60001P); 0.8 parts of polycarboxylate superplasticizer (PCA-100); and 48 parts of water. The designed construction thickness of interface transition layer 3 is 3 mm.
[0046] The preparation process of interface transition layer 3 is as follows: First, silicate cement, quartz sand, redispersible latex powder, and cellulose ether are dry-mixed in a mixer for 2 minutes to ensure that the solid powders are fully and evenly dispersed. Then, γ-glycidyl ether oxypropyltrimethoxysilane is diluted with water and slowly added to the mixer, and mixing continues for 3 minutes. Finally, polycarboxylate superplasticizer is added, and mixing is continued for 2 minutes to obtain a uniform polymer cement mortar. During the mixing process, care should be taken to avoid over-mixing, which may lead to fiber bridging and the introduction of air bubbles.
[0047] The interface transition layer 3 is applied using a notched trowel. The prepared polymer cement mortar is evenly applied to the outer surface of the insulation core layer 2, with a thickness controlled at 3mm. Immediately after application, a notched trowel is used to create notches in the same direction, with a notch depth designed to be 1.5mm. The notches increase the contact area between the mortar and the subsequent waterproof coating, while also providing ventilation channels. After application, the layer is cured for 18 hours at 25℃ and 65% relative humidity.
[0048] The polymer waterproof coating formula for waterproof and seepage-proof layer 4 is designed according to the following parts by weight: 48 parts of acrylic copolymer emulsion (AC-261) with a solid content of 50%; 3 parts of nano silica (AEROSIL 200) with a particle size of 20nm; 4 parts of flaky sericite powder grafted with polyurethane; 5 parts of crystalline active masterbatch (CCCW-C), including 3.5 parts of active calcium silicate and 1.5 parts of active calcium aluminate; 10 parts of sodium methylsiloxane solution (WS-30) with a solid content of 30%; 2 parts of composite slow-release penetration crystallization promoter; 2 parts of film-forming aid (Texanol); 0.3 parts of silicone defoamer (BYK-024); 0.5 parts of polycarboxylic acid dispersant (Disperbyk-190); and 20 parts of water. The designed construction thickness of waterproof and seepage-proof layer 4 is 2.0mm.
[0049] The preparation process of the key modified materials is as follows: Preparation of flaky sericite powder grafted with polyurethane: 100g of flaky sericite powder was dispersed in 500mL of ethanol aqueous solution (volume ratio 1:1), 5g of γ-aminopropyltriethoxysilane was added, and the mixture was stirred at 70℃ for 3h. After filtration and drying at 100℃, aminated sericite powder was obtained. 20g of isocyanate-terminated polyurethane prepolymer was dissolved in 200mL of N,N-dimethylformamide, and the above aminated sericite powder was added. The mixture was reacted at 55℃ for 5h, centrifuged, washed three times with anhydrous ethanol, and dried under vacuum at 60℃ to obtain flaky sericite powder grafted with polyurethane.
[0050] 2. Preparation of composite slow-release permeation crystallization accelerator: Weigh 300g of lithium carbonate and 150g of sodium fluorosilicate, pulverize them through a 200-mesh sieve, and mix them evenly to obtain 450g of solid mixture; weigh 150g of sodium dodecylbenzenesulfonate and dissolve it in 1200g of deionized water to prepare an aqueous solution with a mass fraction of 11.1%; add 450g of solid mixture to the sodium dodecylbenzenesulfonate aqueous solution, ultrasonically disperse for 30min, and then spray dry, controlling the inlet air temperature at 130℃, to obtain a composite slow-release permeation crystallization accelerator with a surfactant coating on the surface.
[0051] The preparation and construction process of waterproof and seepage-proof layer 4 is as follows: First, disperse the acrylic copolymer emulsion and water in a mixing container, and turn on the mixer to stir at a speed of 300-500 rpm. Slowly add nano-silica and surface-grafted polyurethane flake sericite powder while stirring to ensure that the nanoparticles are fully dispersed and avoid clumping. Add the crystallizing active masterbatch and composite slow-release penetration crystallization promoter, and continue stirring for 10 minutes. Then, add the penetration carrier, film-forming aid, defoamer, and dispersant in sequence, stirring for 3 minutes after each aid is added. Finally, add the remaining water to adjust the viscosity and complete the coating preparation.
[0052] The waterproof and seepage-proof layer 4 is applied in two coats. The first coat is 1.0 mm thick and is left to stand for 1-2 hours to allow it to partially dry. The second coat is then applied, also with a thickness of 1.0 mm. The interval between the two coats is designed to be 5 hours, ensuring the first coat is fully dry but not completely cured, which facilitates penetration and bonding between the two layers. After application, the layers are cured for 36 hours at 20°C and 70% relative humidity.
[0053] The stepped flow channels 6 are designed on both sides of the insulation board, running through the height of the insulation board. The cross-section of the flow channels is stepped; in this embodiment, it is designed with two steps. Each step is 1.0 mm deep and 3 mm wide. The steps are processed during the production of the insulation board, using a special molding die to press the stepped shape onto the XPS board.
[0054] A hydrophobic flange 7 is installed at the lower outlet of the stepped flow channel 6. The cross-section of the hydrophobic flange 7 is triangular, with a height of 1.5 mm and a width of 2.5 mm. The flange surface is coated with a superhydrophobic coating, achieving a contact angle of 155 degrees. The superhydrophobic coating uses a commercially available nano-silica modified silane product, diluted according to the manufacturer's instructions, and brushed onto the flange surface. It then cures at room temperature for 24 hours.
[0055] The protective finishing layer 5 consists of a crack-resistant mortar base layer, an alkali-resistant fiberglass mesh, and a finishing layer. The crack-resistant mortar base layer is 3mm thick and uses polymer-modified crack-resistant mortar. The alkali-resistant fiberglass mesh is 160g / m². 2 The specified product is laid after the initial setting and before the final setting of the crack-resistant mortar base layer. The finishing layer uses exterior wall elastic paint or real stone paint, with a thickness of 2mm. The total thickness of the protective finishing layer 5 is designed to be 5mm.
[0056] The construction method in this embodiment includes the following steps: S1. Base Treatment Stage. First, use a broom and high-pressure water gun to clean the surface of the exterior wall base layer, removing loose dust, oil stains, and any loose parts. For any cracks or holes in the base layer, fill them with polymer repair mortar. The mortar mix consists of 100 parts cement, 150 parts fine sand, 20 parts polymer emulsion, and 35 parts water. Allow it to cure for 24 hours after filling. After the entire base treatment is completed, use a moisture meter to test the moisture content of the base layer. Ensure the moisture content is no greater than 8% before proceeding to the next step of construction.
[0057] S2, Marking and Positioning Stage. Mark horizontal and vertical baselines on the base wall. The horizontal baseline should close around the perimeter of the building, and the vertical baseline should run from the roof to the bottom. The intersection error of the two baselines should be controlled within 2mm. Determine the installation position of each insulation board based on the baselines, and mark the board boundary lines on the wall.
[0058] S3. Application of the Base Adhesive Layer (Stage 1): Apply polymer adhesive mortar to the inner surface of the insulation board using a strip application method. The mortar should be applied in strips 10mm wide with a spacing of 20-30mm, covering approximately 45% of the surface area. After application, allow the mortar to stand for 5-10 minutes to allow it to initially harden, increasing its thixotropic and water-retention properties.
[0059] S4. Laying the interface transition layer (stage 3). Prepare the polymer cement mortar containing silane coupling agent according to the aforementioned formula. The coating thickness is 3mm, and after coating, use a notched trowel to create a notch texture with a notch depth of 1.5mm. Cure for 18 hours at a temperature of 25℃ and a relative humidity of 65%. During the curing period, avoid direct sunlight and rain.
[0060] S5. Applying the waterproof and seepage-resistant layer (stage 4). Prepare the polymer waterproof coating containing nano-silica penetrating crystallizing components according to the aforementioned formula. Apply the first coat with a thickness of 1.0 mm, followed by a second coat with a thickness of 1.0 mm after a 5-hour interval. After coating, cure for 36 hours at a temperature of 20°C and a relative humidity of 70%. During the coating process, the nano-silica penetrating crystallizing components penetrate into the capillaries of the interface transition layer 3, achieving a penetration depth of over 5 mm.
[0061] S6. Insulation Board Installation Stage. Apply the coated insulation boards to the base wall surface from bottom to top and from left to right. Press firmly on the insulation boards during application to ensure even distribution of the adhesive mortar and expel air bubbles. The joint width should be controlled within 3mm. The drainage channels 6 of adjacent insulation boards must be aligned and joined to ensure a continuous drainage path. The surface of the insulation boards should be flat, and the height difference between adjacent boards should not exceed 1mm.
[0062] S7. Anchoring and Fixing Stage. Anchors are installed 24 hours after the insulation board is pasted. In this embodiment, 8 anchors are installed per square meter, using plastic expansion anchors. The anchors penetrate the base adhesive layer 1 and the insulation core layer 2 and are anchored into the base wall to a depth of 30mm. The anchor installation position is no less than 50mm from the edge of the board and no less than 100mm from the corner of the board.
[0063] S8. Apply the protective finishing layer in five stages. First, apply a 3mm thick layer of crack-resistant mortar to the outside of the waterproof and seepage-proof layer 4. Then, lay alkali-resistant fiberglass mesh, with an overlap of at least 50mm between mesh layers. Finally, apply the finishing layer using a roller coating process, with a thickness of 2mm.
[0064] S9. Joint Sealing Stage. The joints between the insulation boards are filled with sealant containing a microcapsule self-healing agent. The microcapsule self-healing agent consists of epoxy resin microcapsules encapsulated in urea-formaldehyde resin, at a dosage of 5% of the sealant weight. The microcapsules are designed with a particle size of 120 micrometers and a wall thickness of 3 micrometers. Silicone weather-resistant sealant (SJ-668) is used, and the filling depth is 1.5-2 times the width of the joint. After filling, the surface is rounded into a concave arc.
[0065] Example 2:
[0066] Please see Figure 1-3 The present invention provides a technical solution: This embodiment is designed for building projects with higher waterproofing requirements, and the formula and process parameters have been enhanced. The insulation board size has been adjusted to 1200mm×600mm×60mm, and the thickness of the insulation core layer 2 has been increased to improve the overall insulation effect.
[0067] The second insulation core layer uses extruded polystyrene foam board, with its density increased to 35 kg / m³. 3 The thermal conductivity is 0.030 W / (m·K), and the thickness is increased to 60 mm. The higher density means better compressive strength and lower water absorption.
[0068] The polymer cement mortar formula for interface transition layer 3 is adjusted as follows: silicate cement P·O42.5 is 100 parts; quartz sand is increased to 280 parts; redispersible latex powder is increased to 7 parts; γ-glycidyl ether oxypropyltrimethoxysilane is increased to 3.0 parts, which is the maximum allowable dosage in this invention; cellulose ether is increased to 0.4 parts; polycarboxylate superplasticizer is increased to 0.9 parts; and water is increased to 52 parts. The construction thickness of interface transition layer 3 is increased to 3.5 mm.
[0069] The increased dosage of silane coupling agent in the formulation is due to the following considerations: a higher coupling agent content enables the formation of a denser chemical bond network between the cement matrix and the polymer. The increased number of silanol groups generated after the hydrolysis of the methoxy group in γ-glycidyl etheroxypropyltrimethoxysilane provides more binding sites for calcium ions in the cement hydration products. Simultaneously, the number of epoxy groups also increases, raising the probability of reaction with polymer segments. This dual effect further enhances the interfacial bond strength.
[0070] The polymer waterproof coating formulation for waterproof and seepage-proof layer 4 has also been enhanced: the acrylic copolymer emulsion has been increased to 50 parts; nano silica (AEROSIL 300) has been increased to 5 parts, with a particle size reduced to 15nm; the flaky sericite powder with surface-grafted polyurethane has been increased to 6 parts; the crystalline active masterbatch has been increased to 8 parts, including 5.5 parts of active calcium silicate and 2.5 parts of active calcium aluminate; the penetrating carrier sodium methylsiloxane solution has been increased to 14 parts; the composite slow-release penetrating crystallization promoter has been increased to 3 parts; the film-forming aid has been increased to 3 parts; the silicone defoamer has been increased to 0.5 parts; the polycarboxylic acid dispersant has been increased to 0.8 parts; and the water has been increased to 22 parts. The construction thickness of waterproof and seepage-proof layer 4 has been increased to 2.5mm.
[0071] The preparation process of the key modified materials is as follows: Preparation of flaky sericite powder grafted with polyurethane: 150g of flaky sericite powder was dispersed in 750mL of ethanol aqueous solution (volume ratio 1:1), 7.5g of γ-aminopropyltriethoxysilane was added, and the mixture was stirred at 70℃ for 3h. After filtration and drying at 100℃, aminated sericite powder was obtained. 30g of isocyanate-terminated polyurethane prepolymer was dissolved in 300mL of N,N-dimethylformamide, and the above aminated sericite powder was added. The mixture was reacted at 55℃ for 5h, centrifuged, washed three times with anhydrous ethanol, and dried under vacuum at 60℃ to obtain flaky sericite powder grafted with polyurethane.
[0072] 2. Preparation of composite slow-release permeation crystallization accelerator: Weigh 400g of lithium carbonate and 200g of sodium fluorosilicate, pulverize them through a 200-mesh sieve, and mix them evenly to obtain 600g of solid mixture; weigh 200g of sodium dodecylbenzenesulfonate and dissolve it in 1600g of deionized water to prepare an aqueous solution with a mass fraction of 11.1%; add 600g of solid mixture to the sodium dodecylbenzenesulfonate aqueous solution, ultrasonically disperse for 30min, and then spray dry, controlling the inlet air temperature at 130℃, to obtain a composite slow-release permeation crystallization accelerator with a surface coated with surfactant.
[0073] The particle size of nano-silica decreased from 20nm to 15nm; the surface area increased from approximately 200m². 2 / g increased to approximately 300m 2 / g. Smaller particle size means greater surface area and higher chemical activity. Nanoparticles can enter finer capillaries, increasing the contact area with calcium hydroxide and resulting in a denser hydrated calcium silicate gel. Simultaneously, 15nm nano-silica particles exhibit better dispersibility in coatings and are less prone to aggregation.
[0074] The increased content of the crystalline active masterbatch allows the coating to store more potential crystalline substances. These substances undergo a secondary hydration reaction upon encountering water seepage, generating more ettringite crystals to block the seepage channels. The high content of the permeation carrier ensures that these active substances can be effectively carried into the capillaries of the interface transition layer 3.
[0075] The stepped flow channel 6 has been upgraded to a 3-step design, with each step increasing in depth to 1.2mm while maintaining a width of 3mm. More steps mean a longer water flow path and more energy dissipation points. The water flow slows down and changes direction at each step, resulting in a significant reduction in kinetic energy by the time it reaches the hydrophobic flange 7.
[0076] The height of the hydrophobic flange 7 has been increased from 1.5mm to 1.8mm, while the width remains at 2.5mm. The higher flange provides a larger overhang angle, allowing water to be thrown further. The flange surface is also coated with a superhydrophobic coating.
[0077] Regarding construction method parameters: the moisture content of the substrate is controlled below 7%, which is stricter than in Example 1; the bonding area of the strip bonding method is increased to 50%, close to the maximum value allowed by the specification; the interface transition layer 3 is coated with a thickness of 3.5mm and a tooth depth of 1.8mm, and cured for 20 hours under the conditions of 28℃ temperature and 60% relative humidity; the waterproof coating is applied in two coats with thicknesses of 1.2mm and 1.3mm respectively, with an interval of 5 hours, and cured for 40 hours under the conditions of 20℃ temperature and 70% relative humidity; the anchor bolt insertion depth is increased to 32mm; the microcapsule dosage is increased to 6%, the particle size is reduced to 100 micrometers, and the wall thickness is increased to 4 micrometers.
[0078] The design concept of this embodiment is to further enhance the performance of each functional layer based on Embodiment 1. The high dosage of silane coupling agent ensures the highest strength of interfacial bonding, the refinement treatment of nano-silica improves the penetration and crystallization effect, the multi-stage stepped flow channels 6 optimize the drainage performance, and the parameter adjustment of microcapsules takes into account both repair capability and storage stability.
[0079] Example 3:
[0080] Please see Figure 1-3The present invention provides a technical solution: This embodiment uses molded polystyrene foam board as the insulation core material, which is suitable for projects with special requirements for bonding performance. The surface roughness of molded polystyrene foam board is greater than that of extruded polystyrene foam board, theoretically resulting in better bonding performance. However, this embodiment still employs the interface transition layer 3 technology of the present invention to obtain higher interface bonding strength.
[0081] The insulation board measures 1200mm × 600mm × 50mm. The second insulation core layer uses molded polystyrene foam board with a density of 22kg / m³. 3 The thermal conductivity is 0.032 W / (m·K), and the thickness is 50 mm. EPS board has a lower density than XPS board, resulting in slightly inferior insulation performance, but it is more economical.
[0082] The thickness of the base bonding layer 1 is increased to 5mm, which is thicker than the previous two embodiments. Increasing the thickness of the bonding layer can provide a larger bonding area and a higher safety margin. The compressive strength of the EPS board is lower than that of the XPS board, resulting in greater stress at the anchor points; a thicker bonding layer can better disperse the anchoring stress.
[0083] The polymer cement mortar formulation for interface transition layer 3 is designed as follows: 100 parts of silicate cement P·O42.5; 220 parts of quartz sand; 6 parts of redispersible latex powder; 2.5 parts of γ-glycidyl ether oxypropyltrimethoxysilane; 0.35 parts of cellulose ether; 0.7 parts of polycarboxylate superplasticizer; and 45 parts of water. The construction thickness of interface transition layer 3 is 3 mm.
[0084] Reducing the amount of quartz sand increases the relative cement content in the mortar, which helps to enhance the bond with the base wall. The content of redispersible latex powder is moderate, ensuring flexibility without sacrificing strength. The silane coupling agent content of 2.5 parts is at a medium-high level, which is sufficient considering the good bonding properties of EPS boards themselves.
[0085] The polymer waterproof coating formulation for waterproof and seepage-proof layer 4 is designed as follows: 45 parts acrylic copolymer emulsion; 4 parts nano-silica with a particle size of 20nm; 3 parts flaky sericite powder grafted with polyurethane; 6 parts crystalline active masterbatch, including 4.2 parts active calcium silicate and 1.8 parts active calcium aluminate; 12 parts sodium methylsiloxane solution as a penetration carrier; 1 part composite slow-release penetration crystallization promoter; 2 parts film-forming aid; 0.4 parts silicone defoamer; 0.6 parts polycarboxylic acid dispersant; and 18 parts water. The construction thickness of waterproof and seepage-proof layer 4 is reduced to 1.8mm.
[0086] The preparation process of the key modified materials is as follows: 1. Preparation of flaky sericite powder grafted with polyurethane: 80g of flaky sericite powder was dispersed in 400mL of ethanol aqueous solution (volume ratio 1:1), 4g of γ-aminopropyltriethoxysilane was added, and the mixture was stirred at 70℃ for 3h. After filtration and drying at 100℃, aminated sericite powder was obtained. 16g of isocyanate-terminated polyurethane prepolymer was dissolved in 160mL of N,N-dimethylformamide, and the above aminated sericite powder was added. The mixture was reacted at 55℃ for 5h, centrifuged, washed three times with anhydrous ethanol, and dried under vacuum at 60℃ to obtain flaky sericite powder grafted with polyurethane.
[0087] 2. Preparation of composite slow-release permeation crystallization accelerator: Weigh 200g of lithium carbonate and 100g of sodium fluorosilicate, pulverize them through a 200-mesh sieve, and mix them evenly to obtain 300g of solid mixture; weigh 100g of sodium dodecylbenzenesulfonate and dissolve it in 800g of deionized water to prepare an aqueous solution with a mass fraction of 11.1%; add the 300g solid mixture to the sodium dodecylbenzenesulfonate aqueous solution, ultrasonically disperse for 30min, and then spray dry, controlling the inlet air temperature at 130℃, to obtain a composite slow-release permeation crystallization accelerator with a surface coated with surfactant.
[0088] The reduced thickness of the waterproof layer is based on the characteristics of the EPS board itself. The surface of the molded polystyrene foam board is rough, resulting in better adhesion to the waterproof coating. A thinner waterproof layer saves material costs and reduces overall weight. All waterproof performance indicators still meet design requirements.
[0089] The stepped drainage channel 6 is designed with two steps, with each step reduced to a depth of 0.8mm and a width reduced to 2.5mm. Considering the surface roughness of the EPS board, the size of the drainage channel is appropriately reduced, which ensures drainage function while avoiding excessive weakening of the board strength.
[0090] The dimensions of the hydrophobic flange 7 are also reduced accordingly: 1.2 mm in height and 2 mm in width. The flange surface is also coated with a superhydrophobic coating.
[0091] Regarding construction method parameters: the moisture content of the substrate is controlled below 9%, which is relatively lenient; the dot-frame method is used for construction, and the bonding area is controlled at 45%; the interface transition layer is applied in 3 coats with a thickness of 3mm and a tooth depth of 1.5mm, and cured for 16 hours under the conditions of 23℃ temperature and 70% relative humidity; two coats of waterproof coating are applied, each with a thickness of 0.9mm, with an interval of 5 hours, and cured for 30 hours under the conditions of 20℃ temperature and 68% relative humidity; the number of anchor bolts is reduced to 7 per meter. 2 The anchoring depth is 28 mm; the microcapsule dosage is reduced to 4%, the particle size is increased to 150 micrometers, and the wall thickness is 3 micrometers.
[0092] The dot-frame method involves applying a ring of adhesive mortar around the edge of the insulation board to form a "frame," and then applying adhesive mortar in dots within the frame to form "dots." This method, compared to the strip bonding method, saves approximately 20% of material and is suitable for large-area construction.
[0093] The reduction in microcapsule dosage and the increase in particle size are based on cost optimization considerations. EPS boards typically exhibit less seam deformation, while XPS boards have a relatively lower need for self-healing capabilities. Appropriately reducing the microcapsule dosage can save costs while ensuring basic functional requirements are met.
[0094] The three embodiments share the common feature of employing a γ-glycidyl etheroxypropyltrimethoxysilane interface transition layer 3, a nano-silica penetrating crystallization waterproof layer, a combination of tiered drainage channels 6 and hydrophobic flanges 7, a protective finishing layer 5, and a microcapsule self-healing sealant. The differences between the embodiments lie in the selection of formulation concentration, layer thickness parameters, and board type to adapt to different application scenarios and performance requirements.
[0095] Comparative Example 1: Please see Figure 1-3 The present invention provides a comparative scheme: the only difference between this comparative example and Example 1 is that γ-glycidyl etheroxypropyltrimethoxysilane is not added to the interface transition layer 3 mortar, and the rest of the formulation and process parameters are exactly the same.
[0096] The mortar formula for the interface transition layer 3 is as follows: 100 parts of silicate cement P·O42.5; 250 parts of quartz sand; 5 parts of redispersible latex powder; 0.3 parts of cellulose ether; 0.8 parts of polycarboxylate superplasticizer; and 48 parts of water. This formula, after removing the silane coupling agent, is simply a regular polymer cement mortar.
[0097] The interfacial transition layer 3, with the γ-glycidyl etheroxypropyltrimethoxysilane removed, bonds to the insulation core layer 2 and the waterproof and seepage-resistant layer 4 solely through the physical filling effect of the polymer latex powder and the mechanical interlocking effect of the cement hydration products. The polymer latex powder forms a continuous polymer film within the cement paste, filling the pores of the cement hydration products and providing a certain degree of bridging. However, this bridging is purely physical, and the adhesion between the polymer film and the cement hydration products is limited.
[0098] More importantly, lacking the chemical bonding effect of silane coupling agents, the inorganic cement matrix and the organic polymer coating can only be connected by weak interactions such as van der Waals forces. These weak interactions are weakened or even destroyed when moisture penetrates. When moisture seeps into the interface region, it forms a water film at the inorganic-organic interface, blocking the original physical contact and causing a sharp decrease in interfacial bond strength.
[0099] The test data show that the tensile bond strength of Comparative Example 1 was 0.42 MPa, while that of Example 1 reached 0.68 MPa, representing an increase of approximately 62%. After immersion in water, the bond strength of Comparative Example 1 was only 0.25 MPa, a decrease of 40%; while the bond strength of Example 1 after immersion in water was 0.52 MPa, a decrease of only 24%. After freeze-thaw cycles, the bond strength of Comparative Example 1 dropped even further to 0.18 MPa, approaching the critical value for failure.
[0100] These data strongly demonstrate the irreplaceable nature of γ-glycidyl etheroxypropyltrimethoxysilane. The presence of Si-O-Ca chemical bonds and COC covalent bonds creates a stable chemical bonding network in the interfacial region. This chemical bonding is directional and saturable, unlike physical adsorption which is easily replaced by moisture. Even after prolonged immersion in water or repeated freeze-thaw cycles, the chemical bonding network remains intact, and the interfacial adhesion strength does not experience catastrophic degradation.
[0101] The results of Comparative Example 1 show that the bonding performance of the interfacial transition layer 3 without the silane coupling agent is significantly lower than that of the example containing the coupling agent under various operating conditions. This is precisely the main reason why γ-glycidyl etheroxypropyltrimethoxysilane is the core technical feature of this invention.
[0102] Comparative Example 2: Please see Figure 1-3 The present invention provides a comparative scheme: the only difference between this comparative example and Example 1 is that the waterproof and seepage-proof layer 4 coating does not contain nano silica and crystalline active masterbatch, and is replaced by an equal amount of calcium carbonate CC-600 filler.
[0103] The formulation of the waterproof and seepage-proof layer 4 coating is as follows: 48 parts of acrylic copolymer emulsion; 8 parts of calcium carbonate filler replacing the original 3 parts of nano silica and 5 parts of crystalline active masterbatch; 10 parts of sodium methylsiloxane solution as a permeation carrier; 2 parts of film-forming aid; 0.3 parts of organosilicon defoamer; 0.5 parts of polycarboxylic acid dispersant; and 20 parts of water.
[0104] By replacing nano-silica and crystalline active masterbatch with calcium carbonate filler, the waterproof coating becomes a common polymer cement-based waterproof coating. This type of coating relies on the film-forming properties of the polymer emulsion to block water penetration. After the acrylic copolymer emulsion cures, it forms a continuous polymer film that fills the spaces between pigment and filler particles, creating a relatively dense coating.
[0105] However, this density is limited. The polymer film undergoes micro-shrinkage during drying, forming micropores. Furthermore, the adhesion between the polymer film and the interfacial transition layer 3 is physical, lacking chemical bonding, and will swell and peel off under prolonged water immersion. Calcium carbonate filler is an inert material that does not participate in any chemical reaction and cannot actively repair microcracks.
[0106] The limitations of passive waterproofing are clearly exposed in Comparative Example 2. When microcracks appear in the waterproofing layer, moisture seeps into the capillaries of the interface transition layer 3 along the cracks. Traditional waterproofing coatings cannot seal these capillaries, allowing moisture to continue to penetrate, ultimately leading to failure of the water resistance pressure test. Comparative Example 2's 24-hour water absorption reached 195 g / m³. 2 It is 2.4 times that of Example 1; the anti-seepage pressure is only 0.7 MPa, which is 42% lower than 1.2 MPa of Example 1.
[0107] Regarding the seam leakage rate, Comparative Example 2 showed a rate of 3.8%, indicating that even in the seam area, the use of a waterproof coating without penetrating crystallizing components could not completely prevent moisture penetration. This contrasts sharply with the 0% leakage rate in Example 1.
[0108] More importantly, the test results of the water contact angle of the waterproof layer are most telling. The contact angle of Comparative Example 2 is only 85 degrees, exhibiting almost no hydrophobicity; while the contact angle of Example 1 reaches 128 degrees, demonstrating a significant hydrophobic effect. The fundamental reason for this difference lies in the nanoscale surface roughness of nano-silica itself, which, after combining with the polymer emulsion, forms a micro-nano composite structure, endowing the coating with superhydrophobic properties. Calcium carbonate filler, with its micrometer-level particle size, cannot form nanoscale roughness, resulting in a naturally lower contact angle.
[0109] Comparative Example 2 shows that simple polymer waterproof coatings cannot meet the waterproofing requirements of high-performance exterior wall insulation boards. It is necessary to utilize the penetrating and crystallizing properties of nano-silica to achieve a shift from passive to active waterproofing.
[0110] Comparative Example 3: Please see Figure 1-3 The present invention provides a comparative scheme: the only difference between this comparative example and Example 1 is that the side of the insulation board is a flat surface and there are no stepped flow channels 6 and hydrophobic flanges 7.
[0111] The purpose of this comparative design is to verify the drainage effect of the combined structure of the stepped guide channel 6 and the hydrophobic flange 7. In traditional insulation board designs, side treatment is often neglected. Most manufacturers only treat the surface of the insulation board, while the sides are often just simple cut surfaces without any functional construction.
[0112] The disadvantages of straight sides are obvious. Rainwater falls on the wall and flows along the sides of the insulation board, seeping into the seams under gravity. Without drainage channels to divert the water, the flow concentrates at the seam entrance, creating continuous water pressure. This pressure forces water to continuously seep in, and even if the initial sealant provides a good seal, long-term water pressure will cause the sealant to fatigue and fail.
[0113] The seam leakage rate of Comparative Example 3 reached 8.5%, far higher than the 0% of Example 1. This data shows that relying solely on sealant to prevent water seepage through the board joints is insufficient. An effective drainage system must be used to guide water flow away from the joint inlet, reducing the pressure on the sealant to prevent leakage.
[0114] The multi-stage design of the stepped flow channel 6 causes kinetic energy attenuation at each stage. Experimental observations show that when water flows from one stage to the next, a hydraulic jump occurs at the edge of the stage, and a large amount of kinetic energy is converted into heat and dissipated. When the water reaches the lowest stage, its velocity has decreased significantly. At this point, the water is further guided away from the gap by the jetting effect of the hydrophobic flange 7.
[0115] The triangular cross-section of the hydrophobic flange 7 provides an ideal overhang shape. When water reaches the flange, it is guided away from the panel surface along the flange's inclined surface. The superhydrophobic coating makes it virtually impossible for water to adhere to the flange surface, further ensuring the spillage effect. Even if a small amount of residual water remains on the flange surface, it will roll off under gravity and will not flow down the panel surface and re-enter the panel joint.
[0116] The anti-seepage pressure of Comparative Example 3 was 0.85 MPa, which was 29% lower than the 1.2 MPa of Example 1. This indicates that the stepped drainage channel 6 and the hydrophobic flange 7 can not only prevent water seepage from the board joints, but also reduce the water pressure of rainwater on the insulation board as a whole, thereby reducing the risk of water seepage.
[0117] It is worth noting that Comparative Example 3 is completely identical to Example 1 in terms of interface adhesion and waterproof coating, but its overall waterproof performance is still significantly different. This indicates that the stepped drainage channel 6 and the hydrophobic flange 7, as waterproofing measures at the physical structural level, form an effective complementary relationship with the interface transition layer 3 and the waterproof and impermeable layer 4 at the material level. Without reliable physical water-blocking measures, the burden on the material waterproofing layer will increase; without a reliable material waterproofing layer, the effectiveness of the physical water-blocking measures will also be reduced.
[0118] Comparative Example 4: Please see Figure 1-3 The present invention provides a comparative scheme: the only difference between this comparative example and Example 1 is that the waterproof and seepage-resistant coating 4 does not contain "surface-grafted polyurethane flake sericite powder," but instead uses an equal amount of unmodified ordinary flake sericite powder (i.e., directly weighing 100g of ordinary flake sericite powder and adding it to the coating without silanization and polyurethane grafting modification). All other formulations and process parameters are exactly the same.
[0119] While ordinary flaky sericite powder possesses some water-blocking properties due to its flaky structure, it lacks surface-grafted flexible polyurethane segments, resulting in poor interfacial compatibility with the acrylic emulsion matrix. When the insulation board experiences thermal expansion and contraction caused by diurnal temperature variations, ordinary sericite powder cannot effectively follow the matrix deformation, easily leading to micro-debonding at the edges of the flakes, forming microscopic water-permeable channels, and significantly reducing its crack resistance and water-proofing performance.
[0120] Comparative Example 5: Please see Figure 1-3 The present invention provides a comparative scheme: the only difference between this comparative example and Example 1 is that the composite slow-release penetration crystallization promoter is not added to the waterproof and seepage-proof layer 4 coating, but is replaced by an equal amount of ordinary lithium carbonate powder (i.e., two parts of ordinary lithium carbonate powder are directly weighed and added to the coating, without sodium fluorosilicate compounding and sodium dodecylbenzene sulfonate coating spray drying). The remaining formulas and process parameters are exactly the same.
[0121] Ordinary lithium carbonate, as a traditional coagulant, dissolves and reacts extremely quickly. After application, lithium carbonate rapidly reacts with calcium ions in the interfacial transition layer, causing the penetration crystallization reaction to concentrate on the coating surface. This not only results in severe scaling and whitening on the surface but also quickly clogs the surface capillaries, hindering the penetration of the crystalline active masterbatch into deeper layers, thus significantly reducing the deep-layer anti-permeability effect.
[0122] Example 1: The performance indicators of the standard formulation were at a moderate level in the three examples. Regarding tensile bond strength, the original strength was 0.68 MPa, after immersion in water 0.52 MPa, and after freeze-thaw cycles 0.48 MPa; all three values exceeded the specified requirements of 0.6 MPa, 0.4 MPa, and 0.3 MPa, respectively. The 24-hour water absorption was 82 g / m³. 2 Far below the upper limit of 500g / m 2 A seepage resistance pressure of 1.2 MPa meets the waterproofing requirements of most building projects. A 0% joint leakage rate indicates that the entire waterproofing system is functioning well.
[0123] The synergistic effect between the functional layers is reflected in the following aspects: the interface transition layer 3 provides a solid bonding foundation, preventing the waterproof and seepage-proof layer 4 from peeling off from the thermal insulation core layer 2; the nano-SiO2 penetrating crystal components of the waterproof and seepage-proof layer 4 penetrate into the capillaries of the interface transition layer 3, forming an anchoring effect and further enhancing the interlayer bonding; the stepped drainage channels 6 and the hydrophobic flange 7 guide the side seepage water away, reducing the seepage pressure between the waterproof and seepage-proof layer 4 and the interface transition layer 3; the protective finishing layer 5 provides mechanical protection for the entire system; and the microcapsule self-healing sealant seals the seepage channels at the end.
[0124] Compared to Comparative Example 1, the interfacial bonding strength of Example 1 increased by 62%-167%, indicating that the molecular-level bridging effect of γ-glycidyl etheroxypropyltrimethoxysilane is significant. Compared to Comparative Example 2, the water absorption of Example 1 decreased by 58%, and the impermeability pressure increased by 71%, indicating that the active waterproofing effect of nano-SiO2 penetrating crystallization is irreplaceable. Compared to Comparative Example 3, the joint leakage rate of Example 1 decreased from 8.5% to 0%, indicating that the drainage structure of the stepped drainage channel 6 and the hydrophobic flange 7 is a key design feature.
[0125] Example 2: The high waterproof formula outperforms Example 1 in all performance indicators. The tensile bond strength reaches 0.72 MPa initially, 0.58 MPa after immersion in water, and 0.53 MPa after freeze-thaw cycles, comprehensively exceeding the specifications. The 24-hour water absorption is further reduced to 65 g / m³. 2 The impermeability pressure has been increased to 1.5 MPa, and the water contact angle of the waterproof layer has reached 135 degrees. These improvements are mainly attributed to a higher silane coupling agent content, finer nano-silica particle size, and more than 6 levels of stepped flow channels.
[0126] Example 3: The high-adhesion formulation uses EPS board, and its performance indicators are basically the same as those in Example 1, with slight differences in some indicators. The tensile bond strength is actually higher, reaching 0.75 MPa initially, 0.60 MPa after immersion in water, and 0.55 MPa after freeze-thaw cycles. This is because the EPS board has a higher surface roughness, resulting in stronger mechanical interlocking with the interface transition layer 3. The 24-hour water absorption is 90 g / m³. 2 Slightly higher than Example 1, this is due to the high water absorption rate of the EPS board itself. The impermeability pressure of 1.1 MPa is slightly lower than Example 1, but still at a high level.
[0127] Compared with Comparative Example 4, the tensile bond strength after freeze-thaw in Example 1 increased significantly from 0.26 MPa to 0.48 MPa, and the 24-hour water absorption decreased from 145 g / m³. 2 Significantly reduced to 82g / m 2 The impermeability pressure increased from 0.80 MPa to 1.2 MPa. Comparative Example 4 used unmodified ordinary flake sericite powder, which, while possessing some sheet-like water-blocking properties, exhibited poor interfacial compatibility with the acrylic emulsion matrix due to the lack of surface-grafted polyurethane flexible segments. When the insulation board experienced thermal expansion and contraction (freeze-thaw cycle) caused by diurnal temperature differences, the ordinary sericite powder could not effectively follow the matrix deformation, easily leading to micro-debonding at the sheet edges and forming microscopic water-permeable channels. This data strongly demonstrates the crucial role of the polyurethane flexible segments in the "surface-grafted polyurethane flake sericite powder," which effectively alleviates temperature stress, prevents the formation of micro-cracks, and is the core component for maintaining high crack resistance and impermeability.
[0128] Compared with Comparative Example 5, the impermeability pressure of Example 1 increased from 0.75 MPa to 1.2 MPa, and the 24-hour water absorption increased from 135 g / m³. 2 Reduced to 82g / m 2 Furthermore, Comparative Example 5 exhibited severe scaling and whitening on its surface. Comparative Example 5 used ordinary lithium carbonate instead of the composite slow-release accelerator. Due to the extremely rapid dissolution and reaction rate of ordinary lithium carbonate, it quickly reacted with calcium ions in the interfacial transition layer after application, causing the penetration crystallization reaction to concentrate on the coating surface. This not only caused severe scaling and whitening on the surface but also rapidly blocked surface capillaries, hindering the penetration of the crystallizing active masterbatch into deeper layers, resulting in a significant reduction in deep-layer anti-permeability. This demonstrates that the "composite slow-release penetration crystallization accelerator," achieved through the coating of sodium dodecylbenzenesulfonate surfactant, is a key technology for solving surface scaling and achieving deep-layer directional crystallization.
[0129] Based on the test data from the three embodiments, all technical features of the present invention have performed as intended. The molecular-level bridging effect of γ-glycidyl etheroxypropyltrimethoxysilane stabilizes the interfacial bonding strength at over 0.6 MPa, far exceeding the level of traditional interfacial agents. The nano-SiO2 penetrating crystallization component achieves active waterproofing, maintaining a water absorption rate of 100 g / m³. 2 The combined structure of the stepped drainage channel 6 and the hydrophobic flange 7 reduces the joint leakage rate to 0. Microcapsule self-healing sealant provides intelligent protection for long-term sealing performance. In particular, the introduction of surface-grafted polyurethane flake sericite powder and composite slow-release penetration crystallization promoter completely solves the industry pain points of traditional waterproof layers being prone to cracking and surface scaling during penetration crystallization.
[0130] The synergistic effect of these technical features is not a simple superposition of performance, but rather forms an organic whole that supports and enhances each other. The improved interfacial bonding strength provides a stable adhesion foundation for the waterproof and seepage-resistant layer 4; the flexible sheet-like sericite ensures the integrity of the waterproof layer under deformation; the synergistic effect of nano-penetrating crystallization and slow-release promoter provides permanent and deep sealing of the capillaries in the interfacial region; the tiered flow guide and hydrophobic flange 7 reduce the seepage pressure on the sealant; and the microcapsule self-healing provides a final guarantee at the end. It is this multi-layered, multi-mechanism protective system that enables the waterproof and seepage-resistant performance of this invention to reach a level that is difficult for existing technologies to achieve.
[0131] To further illustrate the beneficial technical effects of the various embodiments of the present invention, relevant performance tests were conducted on Embodiments 1-3 and Comparative Examples 1-3; The testing method is as follows: 1. Tensile bond strength: Prepare bonded specimens measuring 40mm × 40mm × 3mm, with a bonded surface dimension of 20mm × 20mm. After curing the specimens under standard conditions (temperature 23±2℃, relative humidity 50±5%) for 14 days, perform tensile testing using a tensile testing machine at a tensile speed of 5mm / min. Record the maximum failure load and calculate the tensile bond strength based on the bonded area. Prepare 10 specimens for each group, remove the maximum and minimum values, and take the arithmetic mean of the remaining 8 specimens as the test result.
[0132] 2. Tensile bond strength: Specimen preparation and curing conditions were the same as above. After curing for 14 days, the specimens were immersed in water at 20±2℃ for 7 days. After removal, the surface moisture was wiped dry with a damp towel, and the tensile test was completed within 10 minutes. The tensile speed and data processing method were consistent with the original strength test.
[0133] 3. Tensile bond strength: Specimen preparation and curing conditions were the same as above. After 14 days of curing, a freeze-thaw cycle test was conducted. Each cycle consisted of freezing in a low-temperature chamber at -20±2℃ for 4 hours, followed by thawing in water at 20±2℃ for 4 hours. A total of 30 freeze-thaw cycles were performed. After each cycle, the specimen surface was dried, and the tensile test was completed within 2 hours.
[0134] 4. 24-hour water absorption: Prepare 200mm × 200mm finished insulation board specimens, sealing the sides with epoxy resin, leaving only the outer surface as the test surface. Immerse the specimens face down in water at 20±2℃ to a depth of 3mm. After soaking for 24 hours, remove them, wipe the surface dry with a damp towel, weigh the mass difference before and after immersion, and calculate the water absorption per unit area based on the test area.
[0135] 5. Moisture permeability: Prepare a circular specimen with a diameter of 75 mm. Mount the specimen onto a permeation cup using sealant. Fill the cup with desiccant to bring the relative humidity inside to approximately 0%. Place the permeation cup in a constant temperature and humidity chamber at 23±2℃ and 50±5% relative humidity. Weigh the permeation cup every 24 hours for 7 consecutive days. When the deviation of the mass change rate is less than 5% over 3 consecutive days, calculate the moisture permeability based on the stable permeability.
[0136] 6. Permeability Pressure: Tested using a mortar permeameter. Prepare a truncated cone-shaped specimen with an upper diameter of 70mm, a lower diameter of 80mm, and a height of 30mm, and cure it under standard conditions for 28 days. Install the specimen on the permeameter and apply pressure starting from 0.1MPa, increasing by 0.1MPa every 8 hours until water seepage appears at the specimen's end face. Record the water pressure value at this point; this is the permeability pressure. If no water seepage occurs even after pressurizing to 1.5MPa, the test is stopped, and the permeability pressure is recorded as ≥1.5MPa.
[0137] 7. Thermal conductivity: The thermally shielded plate method was used for testing. Insulation board specimens measuring 300mm × 300mm × 50mm were prepared and conditioned for 24 hours at 23±2℃ and 50±5% relative humidity before testing. The specimens were installed between the cold and hot plates of the thermal conductivity meter, with the hot plate temperature set to 35℃ and the cold plate temperature set to 15℃, a temperature difference of 20℃. After the system reached a stable state, the thermal conductivity was calculated based on the heat flux density and temperature difference. Each specimen was measured three times, and the average value was taken.
[0138] 8. Joint Leakage Rate: Prepare 600mm×600mm insulation board assembly specimens. Two insulation boards are installed according to the construction method, and the joints are filled with sealant. Curing is performed for 7 days. The assembly specimen is fixed at a 45° angle, and a spray device is installed above the board surface. The spray water pressure is 0.3MPa, and the spray water flow rate is 2.0L / (min·m). 2 Spray continuously for 4 hours. After spraying, disassemble the specimens and observe whether there are any water seepage marks on the inside of the joints. Measure the area of the seepage area. Joint leakage rate = area of seepage area ÷ total area of joints × 100%. Prepare 3 assembled specimens for each group and take the average value.
[0139] 9. Water Contact Angle of Waterproof Layer: A smooth test surface was prepared on the surface of the waterproof and seepage-proof layer 4. An optical contact angle meter was used, employing the seated drop method for measurement. 3 μL of deionized water was dropped onto the test surface using a micro-syringe. An image of the droplet was acquired within 5 seconds of contact with the test surface, and the contact angle was calculated using the Young-Laplace equation. Measurements were taken at 5 different locations for each specimen, and the arithmetic mean was calculated.
[0140] The above descriptions are merely embodiments of the present invention, and common knowledge regarding specific technical solutions or characteristics is not elaborated upon here. It should be noted that those skilled in the art can make various modifications and improvements without departing from the technical solutions of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the implementation of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.
Claims
1. A waterproof and seepage-resistant building exterior wall insulation board, comprising, from the inside out, a base bonding layer (1), an insulation core, an interface transition layer (3), a waterproof and seepage-resistant layer (4), and a protective finishing layer (5), characterized in that: The interface transition layer (3) is made of polymer cement mortar containing a silane coupling agent, wherein the silane coupling agent is γ-glycidyl etheroxypropyltrimethoxysilane, and its dosage in the polymer cement mortar is 1.5% to 3.0% of the cement weight; The waterproof and seepage-proof layer (4) is formed by coating and curing a polymer waterproof coating containing nano-silica penetrating crystallization components. The nano-silica penetrating crystallization components are composed of nano-silica, crystalline active masterbatch and penetrating carrier in a weight ratio of 1:(1.5~2.5):(2.5~3.5). The insulation board has a pair of opposite sides provided with stepped guide channels (6), which extend along the height direction of the insulation board and have a hydrophobic flange (7) at their outlet end.
2. The waterproof and seepage-resistant building exterior wall insulation board according to claim 1, characterized in that: The polymer cement mortar containing silane coupling agent comprises, by weight: 100 parts silicate cement, 200-300 parts quartz sand, 3-8 parts redispersible latex powder, 1.5-3.0 parts γ-glycidyl ether oxypropyltrimethoxysilane, 0.2-0.5 parts cellulose ether, 0.5-1.0 parts water-reducing agent, and 40-55 parts water.
3. The waterproof and seepage-resistant building exterior wall insulation board according to claim 1, characterized in that: The polymer waterproof coating containing nano-silica penetrating crystallization components comprises, by weight: 40-55 parts of acrylate copolymer emulsion, 2-5 parts of nano-silica, 3-6 parts of flaky sericite powder grafted with polyurethane, 3-8 parts of crystalline active masterbatch, 6-14 parts of penetrating carrier, 1-3 parts of composite slow-release penetrating crystallization promoter, 1-3 parts of film-forming aid, 0.2-0.5 parts of defoamer, 0.3-0.8 parts of dispersant, and 15-25 parts of water; The crystalline active masterbatch is a mixture of active calcium silicate and active calcium aluminate in a weight ratio of (2~4):1; the permeation carrier is a sodium methylsilanolate solution. The preparation method of the surface-grafted polyurethane flake sericite powder is as follows: the flake sericite powder is dispersed in an ethanol aqueous solution, γ-aminopropyltriethoxysilane is added, and the mixture is stirred and reacted at 60-80℃ for 2-4 hours. After filtration and drying, aminated sericite powder is obtained. The isocyanate-terminated polyurethane prepolymer is dissolved in N,N-dimethylformamide, and aminated sericite powder is added. The mixture is reacted at 50-60℃ for 4-6 hours, and then centrifuged, washed, and dried to obtain the surface-grafted polyurethane flake sericite powder. The composite slow-release permeation crystallization accelerator is composed of lithium carbonate, sodium fluorosilicate, and sodium dodecylbenzenesulfonate in a weight ratio of (2-4):(1-2):(0.5-1). Its preparation method is as follows: lithium carbonate and sodium fluorosilicate are pulverized and passed through a 200-mesh sieve, then mixed evenly to obtain a solid mixture; sodium dodecylbenzenesulfonate is dissolved in deionized water to prepare an aqueous solution with a mass fraction of 10%-15%; the solid mixture is added to the sodium dodecylbenzenesulfonate aqueous solution, ultrasonically dispersed evenly, and then spray-dried, controlling the inlet air temperature at 120-140℃, thus obtaining a composite slow-release permeation crystallization accelerator with a surface coated with a surfactant.
4. The waterproof and seepage-resistant building exterior wall insulation board according to claim 1, characterized in that: The thermal insulation core layer (2) is extruded polystyrene foam board or molded polystyrene foam board with a thickness of 30~80mm; The base bonding layer (1) is a polymer bonding mortar with a thickness of 3~5mm; The protective finishing layer (5) consists of a crack-resistant mortar base layer, an alkali-resistant glass fiber mesh, and a finishing layer, with a total thickness of 5~8mm.
5. The waterproof and seepage-resistant building exterior wall insulation board according to claim 1, characterized in that: The cross-section of the stepped guide channel (6) is stepped, including at least two steps, each step having a depth of 0.5~1.5mm and a width of 2~4mm; The hydrophobic flange (7) is a triangular convex strip with a height of 1~2mm and a width of 2~3mm, and its surface is coated with a superhydrophobic coating.
6. The waterproof and seepage-resistant building exterior wall insulation board according to claim 1, characterized in that: The thickness of the interface transition layer (3) is 2~4mm; The thickness of the waterproof and seepage-proof layer (4) is 1.5~3.0mm, and the surface water contact angle of the waterproof and seepage-proof layer (4) is ≥120°.
7. A construction method for a waterproof and seepage-resistant building exterior wall insulation board according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Base treatment: Clean the surface of the exterior wall base, removing loose dust, oil stains and loose parts. Fill cracks and holes with repair mortar and cure until the moisture content of the base is ≤10%. S2. Marking and positioning: Mark the horizontal and vertical baselines on the base wall to determine the installation position of the insulation board; S3. Apply base bonding layer: Apply polymer bonding mortar to the inner side of the insulation board to form a base bonding layer (1). Use strip bonding method or dot frame method for construction. The bonding area is ≥40%. S4. Laying the interface transition layer: Apply polymer cement mortar containing silane coupling agent to the outer surface of the insulation core material layer (2) and cure for 12~24h to form the interface transition layer (3); S5. Apply waterproof and seepage-proof layer: Apply polymer waterproof coating containing nano-silica penetrating crystallization components to the surface of the interface transition layer (3), apply in two coats, with an interval of 4~6 hours between each coat, with a total thickness of 1.5~3.0 mm, and cure for 24~48 hours to form waterproof and seepage-proof layer (4). S6. Install insulation boards: Paste the coated insulation boards onto the base wall surface, with the board joint width controlled at 2~4mm, and align the stepped guide grooves (6) of adjacent insulation boards. S7. Anchoring and fixing: Install anchor bolts on the insulation board. The anchor bolts penetrate the base bonding layer 1 and the insulation core material layer 2 and are anchored into the base wall. The anchoring depth is ≥25mm and the number of anchor bolts per square meter is ≥6. S8. Apply protective finishing layer 5: On the outside of the waterproof and seepage-proof layer (4), apply crack-resistant mortar base layer, lay alkali-resistant glass fiber mesh and finishing layer in sequence to form protective finishing layer (5); S9. Joint sealing: Fill the joints between insulation boards with sealant containing microcapsule self-healing agent. The microcapsule self-healing agent is epoxy resin microcapsules encapsulated in urea-formaldehyde resin. The amount of microcapsules is 3% to 8% of the weight of the sealant.
8. The construction method of the waterproof and seepage-resistant building exterior wall insulation board according to claim 7, characterized in that: In step S4, the coating thickness of the polymer cement mortar containing silane coupling agent is 2~4mm. After coating, a notched trowel is used to scrape out the notched texture, the notched texture depth is 1~2mm, the curing temperature is 5~35℃, and the relative humidity is ≥60%.
9. The construction method of the waterproof and seepage-resistant building exterior wall insulation board according to claim 7, characterized in that: In step S5, the thickness of the first coating is 0.8~1.5mm, the thickness of the second coating is 0.7~1.5mm, and after coating, it is cured for 24~48h at a temperature of 20±2℃ and a relative humidity of ≥65%. The nano-silica penetrating crystallization component penetrates into the capillaries of the interface transition layer (3) after coating, with a penetration depth ≥5mm, and reacts with the free calcium ions in the interface transition layer (3) to generate insoluble calcium silicate crystals, which block the capillary channels.
10. The construction method of the waterproof and seepage-resistant building exterior wall insulation board according to claim 7, characterized in that: In step S9, the sealant containing the microcapsule self-healing agent is composed of silicone sealant and microcapsules, wherein the microcapsules have a particle size of 50~200μm and a wall thickness of 2~5μm; When microcracks with a width of ≤0.3mm appear at the joint of the board, the cracks expand to the microcapsules, causing the microcapsules to rupture and release epoxy resin repair agent. Under the action of ambient moisture, the repair agent is cured, thus achieving self-repair of the microcracks.
